Níveis de adubação no crescimento, índice de vegetação, anatomia e fisiologia de cafeeiros em formação - Menicucci Netto, Pedro (2020)
Coffee production is of great importance for agribusiness, with Brazil being the world's largest producer and exporter of this commodity. Among the managements considered primordial to increase productivity, the rational supply of nutrients in the implementation of the crop stands out. Thus, the objective of this study was to evaluate the vegetative growth, anatomy and physiology of coffee plants in formation, at different levels of fertilization, seeking correlation with the normalized difference vegetation index (NDVI). The experiment was implemented and conducted at the Federal University of Lavras (UFLA), in Lavras - MG, in the Coffee Growing Sector of the Department of Agriculture. The randomized block design (DBC) was used, with six levels of fertilization (10, 40, 70, 100, 130 and 160% of the recommended standard dose), with four repetitions. Between April 2019 and March 2020, plant vegetative growth, physiological characteristics, leaf anatomy and correlations with the normalized difference vegetation index (NDVI). Fertilization with 100% of the recommended fertilization is the safest for the implantation of crops without irrigation, corresponding 80 g of P2O5 per seedling in the planting pit, 20 g of K2O per plant in one year and 5 g of N per plant in each application, at the time of planting and in the first year after implantation, 10 g of K2O per plant in one year and 10 g of N per plant in each application (for phosphorus and potassium levels similar to those of the experimental area). The different levels of fertilization with N, P and K in coffee formation also alter chlorophyll and leaf anatomy indexes.